PENGARUH KOMITE AUDIT, TRANSFER PRICING, DAN POLITICAL CONNECTION TERHADAP TAX AVOIDANCE PADA PERUSAHAAN SEKTOR MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2021-2023 - Murti, Siltia; Dewi Astuti, Tutut (JURNAL ILMIAH EDUNOMIKA, 2025)
The purpose of this study is to analyze the influence of the audit committee, transfer pricing, and political connections on tax avoidance in manufacturing companies within the food and beverage sub-sector listed on the Indonesia Stock Exchange during the 2021–2023 period. This research employs a quantitative method with a descriptive approach and multiple linear regression analysis. The data used consist of secondary data obtained from the financial statements of 15 companies over three years of observation, resulting in a total of 45 observations. The results reveal that the audit committee and political connections have no significant effect on tax avoidance, while transfer pricing has a positive and significant effect. These findings suggest that transfer pricing remains the primary strategy used by companies to minimize their tax burden, whereas the effectiveness of the audit committee and political connections in curbing such practices has yet to be optimized. In conclusion, strengthening the supervision of transfer pricing policies and enhancing the role of the audit committee are essential to promote transparency and improve tax compliance among manufacturing companies. Keywords: audit committee, transfer pricing, political connections, tax avoidance